Epigenetics as a paradigm for cancer treatment: chemically targeting the histone lysine methyltransferase EZH2 - Verma, Sharad K. (Henry Stewart Talks, 2015)
Cancer as an unmet medical need, Epigenetics as a paradigm for treating cancer, Histone lysine methyltransferase EZH2 as a target class example, Development of EZH2 inhibitors